REPRESENTASI KOMUNIKASI BUDAYA “NGARAK PENGANTIN BUAYA PUTIH” DALAM PERUBAHAN SOSIAL MASYARAKAT PADARINCANG - Rahmi Mulyasih; Ahmad Sururi (Profetik: Jurnal Komunikasi, 2017)
As one part of local wisdom, traditional art of Ngarak Pengantin Buaya Putih in Padarincang Village, Serang Regency experienced various dimensions of change in facing social change. The tendency is that people are slowly starting to display the outside culture in the wedding. This indicates a social change in Padarincang society, this social change is characterized by the reluctance of some younger generation to preserve the arts of " Ngarak Pengantin Buaya Putih ". The purpose of this study is to find out how the representation of cultural communication of White Buaya bride in the changes of social change at this time, the identification of efforts made in maintaining the traditional arts of white crocodile bride, the obstacles faced and the model of cultural communication in social change. The method used in this study is phenomenology with data collection techniques using interviews, observation and documentation. The results of the study and discussion show that the interaction and transactional communication model between Padarincang community and the outside community has resulted in the impact of social change which resulted in the local cultural stragnation. Although Padarincang society still strives to maintain the existence of art of " Ngarak Pengantin Buaya Putih " in the middle of social change and communication model that occurs in a responsive and transactional interaction. Various efforts of the stakeholders have been done in maintaining the existence of art of white crocodiles bride like the presence of sanggar, socialization and appreciation of local art displays in various community activities.